The scapegoat of heterogeneity: How fragmentation influences political decisionmaking - Corinna Ahlfeld (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2009)
It is regularly stated that political fragmentation has negative effects on reforms leading to delays or even blockades. This connection is reflected in the 'weak government hypothesis' arguing that fragmented governments create higher budget deficits. Although the assumption seems logical, reviewing theoretical and empirical research on the topic does not completely support this hypothesis. In fact, only few theoretical models concentrate on the impact of fragmentation and empirical findings on the issue are ambiguous. Disentangling the effect is intricate: The definition of fragmentation has various dimensions and every model or empirical study does neglect at least some important factors. In the following I would like to shed some light on the relation and the shortcomings of recent findings. As fragmentation will have various effects on political actions it seems unjustified to generally make it the scapegoat of reform delays.
Keywords: H3; D7; H10; 330; political economy; reform delay; fragmentation